Strategi Bisnis Produk Kopi Fresh Tas Sebagai Peluang Wirausaha Di Lingkungan Olahraga - Alya Andini; Chaeris sinaga; Ijon Mulasius Purba; Zen Lugo Manurung; Nehemia sinambela; Richard Paulus sinaga; Agustin Sastrawan Harahap; Nur Kholilah Harahap (CV. ITTC INDONESIA, 2026)
This study aims to analyze the business strategy of “kopi fresh tas” as an entrepreneurial opportunity in the sports environment. The research employed a quantitative approach using a survey method involving 100 respondents who actively engage in sports activities. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression.The results indicate that business strategies, including product innovation, packaging, pricing, and promotion, have a positive effect on consumers’ purchase intention. Kopi fresh tas is perceived as practical, portable, and suitable for active lifestyles. In addition, marketing through social media and sports communities has proven effective in increasing product attractiveness. In conclusion, kopi fresh tas has strong potential as an innovative business that supports a healthy lifestyle and offers promising market opportunities.